Medicinal Plants of Cachar District of Assam Used by the 'Rongmai' Tribe - Ibemhal Chanu, L.; Panwar, G. S.; Baruah, M. K. (Indian Forester, 2015)
An ethnobotanical survey of plants used by the 'Rongmai' tribe for the treatment of various diseases was carried out in the Mashkall village, Lakhipur sub-division of Cachar district of Assam. Information on the names of plants, part used and methods of preparation was collected through a questionnaire which was administered by the local herbalists, traditional healers and rural dwellers. Information collected has revealed 16 plant species belonging to 15 families have been found to be utilized for 48 diseases.